Methods of Developing Rhythmic Skills in Students through Rhythmic Exercises and Dance Movements in Higher Education - Mamajonov Ulugbek Mahammattolibovich (International Journal on Orange Technologies, 2021)
Archaeological excavations in a number of regions of Uzbekistan show that spirituality and culture, especially art, have deep roots here. In the traditional analysis of the culture, in particular, the art of our country, the monuments of Tuprakkala and Koykirildiqala, one of the major centers of the great Khorezmshah state, play an important role. Based on the results of the research, the article describes the methods of developing rhythmic characteristics in students through rhythmic exercises and dance movements in higher education.